Language Education - Mahdum, Mahdum (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
Language plays an important role in the life of nation and state. It cannot be eliminated in human civilization. Indonesia has 742 languages spoken throughout the archipelagos. This situation puts Indonesia as one of the most diverse countries in the world. However, as the unifying language, Indonesia has one language, namely Bahasa Indonesia. Thus, studying the language as well as language education is very important for all people of Indonesia. This article discusses about the important roles of Language Education in Plural Society, Language Education in the 21st Century, and Language Education in Facing MEA. By realizing the importance of the language, Indonesian people will not leave behind people from other countries in the progress of Science and Technology